The Role of Natural Deep Eutectic Solvents in a Hydrogel Formulation Containing Lidocaine - Feria Hasanpour; Mária Budai-Szűcs; Anita Kovács; Rita Ambrus; Orsolya Jójárt-Laczkovich; Boglárka Szalai; Branimir Pavlić; Péter Simon; Levente Törteli; Szilvia Berkó (Pharmaceutics)
Background/Objectives: This study investigates the use of natural deep eutectic solvents (NADESs) in enhancing the solubility and skin permeation of a lidocaine base, a lipophilic form, in hydrogel systems. The aim was to develop an environmentally sustainable and biocompatible alternative to conventional lidocaine formulations, improving the dermal permeation and therapeutic efficacy. Methods: The lidocaine base was dissolved in a hydrophilic NADES system composed of choline chloride and citric acid, facilitating enhanced solubility, likely through new molecular interactions. Then, pH-adjusted hydrogels were formulated and optimized by employing a 32 full factorial design. Raman and nuclear magnetic resonance (NMR) spectroscopy were applied to evaluate the stability of lidocaine in the optimal formulation. The biopharmaceutical properties were investigated using in vitro drug release and skin permeation studies. In vivo tests assessed physiological skin parameters such as the hydration and transepidermal water loss. Results: The developed NADES-containing hydrogel significantly improved the solubility and stability of lidocaine. Skin permeation studies demonstrated enhanced dermal permeation compared with conventional hydrogel and ointment. These improvements, namely the enhanced solubility of lidocaine in the formulation and its increased permeation, were attributed to the dual effect of the NADES. Conclusions: NADES-containing hydrogels represent a promising green technology for formulating lidocaine-containing dermal preparations. This approach offers a biocompatible, natural-based alternative that can enhance the bioavailability and efficacy of topical anesthetics.